PEMBELAJARAN BERBASIS PRAKTIKUM PADA KONSEP INVERTEBRATA UNTUK PENGEMBANGAN SIKAP ILMIAH SISWA - Hayat, Muhammad Syaipul (BIOMA, 2011)
PEMBELAJARAN BERBASIS PRAKTIKUM PADA KONSEPINVERTEBRATA UNTUK PENGEMBANGAN SIKAP ILMIAH SISWA Muhammad Syaipul HayatProgram Studi Pendidikan Biologi IKIP PGRI Semarang Sri Anggraeni dan Sri RedjekiProgram studi Pendidikan IPA Sekolah Pascasarjana UPI e-mail: fullsmile_84@yahoo.com PRACTICUM BASED LEARNING ON INVERTEBRATE CONCEPT TO STUDENTS SCIENTIFIC ATTITUDE DEVELOPMENT ABSTRACT This study aims to develop students scientific attitude, and to identify responses ofteachers and students in practicum based learning on the concept of Invertebrates. Research using the method of quasi experiment with the static group pretest-posttestdesign involving 64 high school students the second semester of class X, whichconsists of 32 students grade class experiment, and 32 students on the control of onhigh school in the Cimahi city of Bandung. Practicum based learning is to orient andtrain students to formulate problems, conduct investigations, solve problems andreflect the results of the investigation. Research data captured by using a test instrumentshapedscientificattitudelikert scale, students questionnaire responses, observationsheets,andinterviews.The results showed that the scientific attitude of students who use practicum basedlearning differ significantly with students who learn in the conventional. These resultsare evidenced by the N-gain students scientific attitude control class of 0.13while the N-gain experimental class scientific attitude is better than the control class,which is 0.33. Based on questionnaire responses of students concluded that studentsliked the practicum based learning, because it can facilitate in understanding thesubject matter, invites students to actively and build cooperation among students.The results of the observation sheet analysis showed activity and positive studentattitudes toward lab activities. Interviews with teachers also showed positive responsestopracticumbasedlearning.The conclusion is practicum based learning had a positive impact in developingscientific attitude students.Keywords: learning, practicum, scientific attitude, students, invertebrate ABSTRAK Salah satu masalah yang dihadapi dunia pendidikan kita adalah masih lemahnyaproses pembelajaran, siswa kurang didorong untuk mengembangkan kemampuanberpikir. Penelitian ini bertujuan untuk mengembangkan sikap ilmiah siswa, sertamengidentifikasi tanggapan guru dan siswa dalam pembelajaran berbasis praktikumpada konsep invertebrata.Penelitian menggunakan metode eksperimen dengan desain quasi eksperimen thestatic group pretest-posttest design yang melibatkan 64 siswa SMA kelas X semesterII, yang terdiri atas 32 siswa kelas eksperimen dan 32 siswa kelas kontrol pada salahsatu SMA swasta di kota Cimahi Bandung. Hasil penelitian menunjukkan bahwa sikap ilmiah siswa yang menggunakan pembelajaranberbasis praktikum berbeda secara signifikan dengan siswa yang belajarsecara konvensional. Hasil tersebut dibuktikan dengan N-gain sikap ilmiah siswakelas kontrol 0,13 sedangkan N-gain sikap ilmiah siswa kelas eksperimen lebih baikdaripada kelas kontrol, yaitu 0,33. Kesimpulannya ialah, pembelajaran berbasis praktikum berdampak positif dalammengembangkan sikap ilmiah siswa.Kata-kata kunci: pembelajaran, praktikum, sikap ilmiah, siswa, invertebrata